The Levy System in East Bengal and its Impact on the Peasantry (1949-1967) (Journal of the Asiatic Society of Bangladesh, Humanities, 2024)
The peasants of Bengal have been living through exploitation since ancient times. The intensity of exploitation of farmers increased manifold from the ancient period to the colonial period. The main reason for this was that on the one hand, the land tax or rent paid to the state during the pre-British period was increased many times and on the other hand, apart from rent, many kinds of abwabs were levied on the peasants. During the British era, the farmers thought that this exploitation and deprivation would end if the country became independent. But after the departure of the British in 1947, in the independent state of Pakistan, the farmers of East Bengal were subjected to exploitation and oppression as in the colonial period. During the Pakistan period, like the British period, the taxes and abwabs paid to the state were increased. Moreover, the levy system, a unique type of agricultural land tax that was assessed based on the total production of the farmer's total land, was introduced by the Muslim League government. As a result, the level of exploitation and oppression of the farmers of East Bengal increased manifold during the Pakistan period. Based on primary and secondary sources, this paper attempts to provide a comprehensive understanding of the introduction of the levy system and investigate its impact on the farmers. The paper will also shed light on  the reactions of politicians and peasants to this newly introduced levy system in East Bengal during the Pakistan period.Journal of the Asiatic Society of Bangladesh (Hum.), Vol. 69(1), 2024, pp. 107-121